Writing cases to advance wine business research and pedagogy - Armand Gilinsky; Sharon L. Forbes; Marlene M. Reed (Wine Economics and Policy, 2016)
This paper is meant to open a dialogue about the elements that constitute an outstanding wine business case study and, if used for teaching purposes, an instructor's manual. The ability to understand, synthesize, evaluate, and also create cases is becoming an increasingly important career-building skill for graduates of higher education programs across all disciplines. First we examine the market for wine business cases, and we then provide a step-by-step guide to the development of cases specifically targeted for wine business education.
Keywords: 330; Case research; Case writing; Wine business